From “Green Building” to Architecture Integrated with Nature: The Principle of Environmental Interconnection - Logvinov, Victor (project baikal, 2017)
As a follow-up to the theme of integration between architecture and nature discussed in the previous issues of Project Baikal, the article gives a definition of the principle of environmental interconnection. It also presents the geneses and the state-of-the-art of the ideas and practices based on this complex and dialectically contradictory principle. The author analyses the evolution of different ways of penetration of natural environment into the inner space of architectural structures. He also studies the development of the idea of openness of architectural structures toward natural environment, including the means of differentiation and regulation of openness and transformable facades and roofs.
Keywords: integration with nature; atriums; winter gardens; double facade; openness; closedness; differentiation; regulated openness; transformable roof and facades